The Settlement of Match-Fixing Cases in Indonesia Based on Progressive Law Enforcement - Robiatul Adawiyah; Suteki Suteki (Universitas Slamet Riyadi, 2020)
Fair play in soccer matches is injured by match-fixing case. So far, form of law enforcement in Indonesia is limited to disciplinary law enforcement. Indonesia is again shocked by match-fixing case in League 3 match in Banjarnegara. Therefore settlement of this is very important to be studied with progressive law enforcement approach. There are two questions that can be raised, namely how the settlement of match-fixing cases and how it based on progressive law enforcement. The research method used is normative. The results showed there are 6 cases with 7 perpetrators, namely Case Number 47/Pid.Sus/2019/PN BNR jo. Number 48/Pid.Sus/2019/PN BNR jo. Number 49/Pid.Sus/2019/PN BNR jo. Number 50/Pid.Sus/2019/PN BNR jo. Number 51/Pid.Sus/2019/PN BNR jo. Number 463/Pid.B/2019/PN JKT.SEL. Although law enforcement has shown progressiveness with success that offenders be punished, settlement of the case still far from expectation of progressive law enforcement that able to provide substantive justice and people's happiness.